2007
DOI: 10.1108/14684520710773050
|View full text |Cite
|
Sign up to set email alerts
|

A tale of information ethics and encyclopædias; or, is Wikipedia just another internet scam?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 1 publication
0
16
0
2
Order By: Relevance
“…Criticism of Wikipedia has also been raised in the academic world. Gary Gorman, for example, argues that Wikipedia is an “unethical resource unworthy of our respect” (Gorman, 2007, p. 274). And the entire history department of Vermont's Middlebury College has officially banned the use of Wikipedia in student papers, noting on its syllabi that “whereas Wikipedia is extraordinarily convenient and, for some general purposes, extremely useful, it nonetheless suffers inevitably from inaccuracies deriving in large measure from its unique manner of compilation” (Read, 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Criticism of Wikipedia has also been raised in the academic world. Gary Gorman, for example, argues that Wikipedia is an “unethical resource unworthy of our respect” (Gorman, 2007, p. 274). And the entire history department of Vermont's Middlebury College has officially banned the use of Wikipedia in student papers, noting on its syllabi that “whereas Wikipedia is extraordinarily convenient and, for some general purposes, extremely useful, it nonetheless suffers inevitably from inaccuracies deriving in large measure from its unique manner of compilation” (Read, 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As a result, it has been suggested that “it's the blind leading the blind—infinite monkeys providing infinite information for infinite readers, perpetuating the cycle of misinformation and ignorance” (Keen, 2007, p. 4). Wikipedia also has been dismissed as unreliable by members of the library and information science community (e.g., Cronin, 2005; Gorman, 2007). The ultimate worry here is that people are likely to acquire false beliefs rather than knowledge as a result of consulting such a seemingly unreliable information source.…”
Section: An Epistemic Evaluation Of Wikipediamentioning
confidence: 99%
“…Moreover, at least a third of American Internet users consult Wikipedia and a majority of those with a college degree (Rainie & Tancer, ). Nevertheless, there have been concerns about the accuracy and completeness of Wikipedia articles (Chesney, ; Denning, Horning, Parnas, & Weinstein, ; Gorman, ; cf. Giles, ) because anonymous authors may add incorrect information (Mehegan, ).…”
Section: Introductionmentioning
confidence: 99%